Characteristics of source rocks, resource potential and exploration direction of Sinian-Cambrian in Sichuan Basin, China - Guoqi Wei; Zhihong Wang; Jian Li; Wei Yang; Zengye Xie (Journal of Natural Gas Geoscience, 2017)
The Anyue giant gas field was discovered in the Sinian-Cambrian Central Sichuan region of the Sichuan Basin in 2013, with geological reserves up to 1 × 1012m3, which is the first time for the exploration of natural gas paleo-reservoirs in the world. The gas source studies suggest that the Sinian natural gas is originated from the Sinian and Cambrian hydrocarbon source rocks, and the systematical study on the Sinian and Cambrian ancient source rocks has important scientific and practical significance for the global oil and gas geologic domain of the ancient stratum. Based on the drilling data and field profile observation of Sinian and Cambrian in Sichuan Basin, with adoption of the interpretation data of 28000 km-seismic and new drilling data, combined with geochemical analysis of source rocks of 2315 samples, this paper systematically studied the high quality hydrocarbon source rock center, where the source rocks are mainly distributed along the Mianzhu-Changning craton inner rift, with a accumulative thickness reaching 200–450 m, and 50–100 m for the thickness of source rocks in other areas. The hydrocarbon source rocks of the Sinian-Cambrian contributed about 56 %–63% of natural gas resources of the whole basin. Systematical evaluations have been conducted to the mudstone source rocks and their distribution in the III-section of Sinian Dengying Formation, where TOC value is ranging from 0.04% to 4.73%, with an average of 0.65%. The thickness of the source rocks in Central Sichuan region is ranging from 10 to 30 m. The oldest Sinian source rocks that can form large gas fields in China were systematically studied for the first time, and the total gas production intensity of the Sinian source rocks in the great Central Sichuan region is (15–28) × 108 m3/km2, where the gas source conditions for the formation of large gas fields are available. By using the genetic method and analogy method, the amount of natural gas resources of the Sinian-Cambrian in the basin are re-evaluated as (4.65–5.58) × 1012 m3, and the resources potential of natural gas is huge. The amount of natural gas resources in the Central Sichuan block accounts for about 66% of the total basin resources, which is the preferred selection for current exploration. Keywords: Source rocks, Resource potential, Sinian, Cambrian, Sichuan Basin